Evaluation of mandibular condyle shape distribution using digital panoramic images - ÖNEM ÖZBİLEN, ELVAN; TURAN, BEGÜM; ABUHAN, ECE (My University, 2023)
Objective: The human condyle is capable of remodelling over time as numerous factors such as age, sex, occlusal force, malocclusion, and skeletal relationship influence this remodelling. This change in shape can lead to the numerous symptoms of degenerative joint disease. The aim of this study was to investigate the different morphologies of the condyle in different age groups at the Faculty of Dentistry, …. University, …., using orthopantomography.Material and Method: A total of 681 panoramic radiographs obtained for this study. The study group consists of 399 female and 282 male individuals aged between 15-55 years. Articular eminence and glenoid fossa regions of the mandibular condyle was traced. The mandibular condyle morphology was classified into six types such as oval, birdbeak, diamond, flat, crooked finger and bifid. Intergroup differences were evaluated with Chi-square and McNemar tests. (p<0.05)Result: A total of 1362 right and left condyles of 681 patients were examined. The most common shape among the six condylar types -regardless of age and gender- was oval condylar morphology, followed by flat, diamond-shaped, crooked finger, birdbeak, and bifid.Conclusion: As a result of the examination of condyle shapes in individuals with different ages on panoramic radiographs, the process of remodelling of the temporomandibular joint condyle over time was observed. The differences found between the age groups are interpreted to be related to the cumulative increase in the amount of functional loading to which the condyle is exposed with increasing age.

Amaç: Temporomandibular eklem kondili, yaş, cinsiyet, oklüzal kuvvet, maloklüzyon ve iskeletsel patern gibi birçok sayıda faktörün etkisiyle zaman içinde yeniden şekillenebilmektedir. Kondil şeklinde oluşan bu değişiklik, dejeneratif eklem hastalığının çeşitli semptomlarına yol açabilir. Bu çalışmanın amacı, Marmara Üniversitesi Diş Hekimliği Fakültesi’ne başvuran hastalarda farklı yaş gruplarında mandibuler kondilin farklı morfolojilerini panoramik radyografi yardımıyla araştırmaktır. Gereç ve Yöntemler: Toplam 681 panoramik radyografi ile yapılan bu çalışmada, çalışma grubu 15-55 yaş arası 399 kadın ve 282 erkek bireyden oluşmaktadır. Mandibular kondilin artiküler eminens ve glenoid fossa bölgeleri incelenerek şekilleri belirlenmiştir. Mandibular kondil morfolojisi oval, kuş gagası, elmas, düz, çarpık parmak ve bifid olmak üzere altı tipte sınıflandırılmıştır. Gruplar arası farklar Ki-kare ve McNemar testleri yardımıyla analiz edilmiştir. (p<0,05) Bulgular: 681 hastaya ait toplam 1362 sağ ve sol kondil incelenmiştir. Altı kondil tipi arasında yaş ve cinsiyet farkı gözetmeksizin en yaygın görülen şekil oval kondil morfolojisi olarak saptanırken, bunu sırasıyla düz, elmas, çarpık parmak, kuş gagası ve bifid kondil şekilleri izlenmiştir. Sonuç: Farklı yaşlardaki bireylerde kondil şekillerinin panoramik radyograflarda incelenmesi sonucunda, temporomandibular eklem kondilinin zaman içinde yeniden şekillenme süreci gözlenmiştir. Yaş grupları arasında tespit edilen farklılıkların, bireyin artan yaşı ile birlikte kondilin maruz kaldığı fonksiyonel yükleme miktarının birikimsel artışı ile ilişkili olduğu düşünülmektedir.
Temporomandibuler eklem kondil şekillerinin dağılımlarının dijital Panoramik radyograflar ile incelenmesi
Keywords: Diş Hekimliği; Klinik Bilimler; Ortodonti; Sağlık Bilimleri; Dentistry; Clinical Sciences; Orthodontics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Kondil şekli; mandibular kondil; ortopantomogram; Condyle shape; mandibular condyle; orthopantomogram